Erosion gastroduodenite – as a complication after operation in perforate ulcer patients - Smetskov, D. A.; Yavorskaya, T. P.; Goncharova, N. N. (Journal of Education, Health and Sport, 2017)
The surgical treatment for perforated peptic ulcer is still a matter of discussion. The surgeons, for many years, made their options between acid-reducing procedures with some morbi-mortality and simpler procedures like closure of the perforation. But, in these cases, were faced with a high chance of ulcer relapse. The origin reasons of one of the most serious complications after operation – the erosion gastroduodenite were revealed on the basis of investigation of 143 patients during 1 – 5 years who were operated with the perforate ulcer diagnosis. The optimum ways of prophylaxis and treatment of the given complication are outlined.